Ableism in academic knowledge production - Compes, Natascha (My University, 2021)
The article takes up feminist disability scholars’ request for an integration of disability (theory) into women’s and gender studies and intends to take stock of the status and development of this integration. By means of qualitative content analysis, excerpts of German and US handbooks of gender research are examined for their degree of integrating disability (theory) and for inherent ableism. Considering the scholars’ requests of full integration and a subsequent transformation of gender research the sample shows only minor signs of change and the request must be upheld.
Keywords: ableism; Ableismus; Behinderung; disability; epistemology; feminist disability studies; gender research; knowledge production; Wissenschaft; ddc:370